Best Answer

Minus a negative means you can plus a positive so therefore the answer would be positive 8.

More answers

(+2) - (-6) = +8

Q: What is positive 6 minus negative 2?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

0

It depends. (a) a positive minus a smaller positive is positive, (b) a positive minus a positive of the same size is zero, and (c) a positive minus a bigger positive is negative. For example, (a) 8 - 6 = 2 (b) 8 - 8 = 0 (c) 8 - 11 = -3

A negative minus a negative turns the latter into a plus positive,for example -6 minus -3 would be :-6 ++ 3 = -3A minus negative always turns into a plus positive...To get more Specific:Suppose x and y are two POSITIVE numbers so that -x and -y are negative. Then a negative minus a negative = (-x) - (-y) = -x +yIf x > y the answer is negativeIf x = y the answer is zeroIf x < y the answer is positive

A minus minus a minus will give a positive result. It will depend on the actual values. It will cause a positive movement, but still could result in a negative number. Consider these two examples. In both cases there is a positive movement but only the second results in an actual positive number:-6 - -2 = -4-2 - -6 = 4

3

Related questions

Negative 4 minus positive 2 is equal to negative 6.

negative read this : "MULTIPLICATION: minus times minus is plus (negative x negative = positive).....minus times plus is minus (negative x positive = negative).....plus times plus is plus (positive x positive = positive) DIVISION: minus divi minus is plus (negative ÷ negative = positive)......minus divi plus is minus (negative ÷ positive = negative).....plus divi plus is plus (positive ÷ positive = positive)"

-6

if a positive number minus a negative number, the minus turns to a plus sign. so its positive Ex. 2- -4= 2+4=6

0

It depends. (a) a positive minus a smaller positive is positive, (b) a positive minus a positive of the same size is zero, and (c) a positive minus a bigger positive is negative. For example, (a) 8 - 6 = 2 (b) 8 - 8 = 0 (c) 8 - 11 = -3

No. If x = -2, then y = -(2x) -(+6) = -2*(-2) - 6 = +4 - 6 = -2

It is: 10--6 = 16 because --6 is +6

positive 5 minus positive 11 = negative 6

Seven minus -6 is 13.

Six because 2 --4 = 6

-6